ENTREPRENEURIAL KNOWLEDGE, ATTITUDES AND PERCEPTIONS AMONG UNDERGRADUATES PHARMACY STUDENTS IN SELANGOR, MALAYSIA - Mohd Eddy Ratyal, Nur Edlynn Shahirah; Husaini, Nur Eliyah; Maniam, Sandra; Ali, Aida Azlina (Journal of Islamic, Social, Economics and Development, 2024)
The role of entrepreneurship is vital in driving economic development and fostering innovation. However, there is a lack of exploration into the extent of entrepreneurial knowledge, attitudes, and perceptions among pharmacy students, especially in the context of Malaysia. Understanding these factors is crucial to instilling an entrepreneurial mindset and equipping students with various career opportunities in the ever- evolving pharmacy field. This study aims to determine the extent of knowledge, attitudes, and perceptions of pharmacy students from the UiTM Selangor towards entrepreneurship and to compare the knowledge, attitudes, and perceptions towards entrepreneurship between first-year and final-year pharmacy students. This study employed a cross- sectional survey method. Three hundred and twelve undergraduate pharmacy students responded to a structured questionnaire using the Likert scale. The questionnaire consisted of four sections with 29 items. The questionnaire was tested for content validity and achieved a high reliability score with a Cronbach's Alpha of 0.93. The survey was conducted from March to May 2024. The outcomes were analyzed to compute mean scores, and an independent samples t-test was conducted using SPSS version 28.0. Pharmacy students have shown a strong understanding of entrepreneurship, scoring notably high in entrepreneurial vision, risk-taking, leadership, communication skills, and workplace environment awareness. The overall knowledge and attitudes towards entrepreneurship were positive. However, perceptions were generally neutral across student cohorts. Statistical analysis indicated significant differences in knowledge and perceptions between first-year and final- year students, highlighting on how academic progression significantly impacts the way students understand and perceive entrepreneurship. Pharmacy students have positive level of knowledge and attitudes but neutral perceptions toward entrepreneurship. Final-year students significantly show better knowledge but less positive attitudes and perceptions towards entrepreneurship. Continuous and practical entrepreneurial education throughout the pharmacy program is important to sustain and enhance positive knowledge, attitudes, and perceptions of entrepreneurship among students.